2014
DOI: 10.1017/s0029665114001657
|View full text |Cite
|
Sign up to set email alerts
|

Control of appetite and energy intake by SCFA: what are the potential underlying mechanisms?

Abstract: In recent years, there has been a renewed interest in the role of dietary fibre in obesity management. Much of this interest stems from animal and human studies which suggest that an increased intake of fermentable fibre can suppress appetite and improve weight management. A growing number of reports have demonstrated that the principal products of colonic fermentation of dietary fibre, SCFA, contribute to energy homeostasis via effects on multiple cellular metabolic pathways and receptor-mediated mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
169
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(181 citation statements)
references
References 101 publications
(147 reference statements)
5
169
0
Order By: Relevance
“…The production of SCFAs by microbial fermentation of dietary fibers is associated with a wide range of health benefits, including improvements in body composition, energy homeostasis, lipid profiles and reduced body weight, by stimulating multiple hormonal and neural pathways, such as appetite control, enhancement of oxidation and thermogenesis in muscle and liver tissues, and others6131415242526. However, no consistent conclusions have been reached on changes of gut SCFA production in obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of SCFAs by microbial fermentation of dietary fibers is associated with a wide range of health benefits, including improvements in body composition, energy homeostasis, lipid profiles and reduced body weight, by stimulating multiple hormonal and neural pathways, such as appetite control, enhancement of oxidation and thermogenesis in muscle and liver tissues, and others6131415242526. However, no consistent conclusions have been reached on changes of gut SCFA production in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous physiological and clinical studies have demonstrated that SCFAs are also a significant source of calories and have trophic effects on both the small and large bowel. Meanwhile, SCFAs may play beneficial roles in appetite regulation and lipid and glucose metabolism by epigenetically regulating related genes1314. SCFAs also act as signal transduction molecules and bind and activate orphan G-protein-coupled receptors, such as GPR43 and GPR41, which are also known as free fatty acid receptor 2 and 3 (FFAR2 and FFAR3), respectively.…”
mentioning
confidence: 99%
“…Although no mechanism has been identified, and studies show conflicting results [38], elevated serum propionate concentrations have been shown to have a hypocholesterolaemic effect [39]. Propionate may also play an influential role in satiety, although mechanisms still remain unclear [40,41]. Cholesterol-lowering properties of beta-glucans may be limited to effects from the upper-GI, although many propionate-producing bacteria have a preference to fermenting various types of beta-glucans (Bacteroides, Prevotella, Clostridium) based on the presence of genes responsible for endo-β-glucanase enzyme production [42].…”
Section: Discussionmentioning
confidence: 99%
“…SCFA production, principally acetate, propionate, and butyrate, is increased in obesity, in both animal models and humans [58]. SCFAs exert multiple beneficial effects on the host energy metabolism not only by improving the intestinal cell differentiation and proliferation but also by directly affecting various host peripheral tissues [59]. SCFAs, indeed, influence energy intake and metabolism through their binding to 2 G-protein-coupled receptors, free fatty acid receptor 2 (FFAR2 or GPR43) and free fatty acid receptor 3 (FFAR3 or GPR41) [60].…”
Section: Gut Microbiota In Obesitymentioning
confidence: 99%